Antecedents of philanthropic behavior of health care volunteers - Alias, Siti Noormi; Ismail, Maimunah (Emerald Group Publishing Limited, 2015)
Purpose This paper aims to propose a conceptual model of philanthropic behavior of volunteers in the health care sector.